Opportunities and Challenges of Reverse Mortgage Scheme in Indian Scenario - Nagar, Amee; Mahesh, N (International Journal of Computer Sciences and Engineering, 2025)
Major part of a person’s lifetime savings is used to buy or build a house; hence, people are emotionally attached with their property. Senior Citizens are a growing section of the society and dependency in old age is increasing. They need a retirement plan/regular case flow stream for supplementing pension/other income and addressing their financial needs. Reverse mortgage is a welcome instrument that helps them convert some or all of their rising but locked home equity into a cash stream that can comfortably sustain them in their old age. In many developed country reverse mortgage loan scheme is very famous. Despite having many advantages and global acceptability, reverse mortgage has not managed to captivate the Indian market because of multiple reasons. It is expected that this scheme will grow after few years in India. Age group of more than 40 years is interested in this scheme as they believe that this scheme will be helpful in their old age. This paper studies opportunities and challenges faced by mortgage industry in lieu of reverse mortgage scheme in India.